Slope Stability Analysis Using GeoStudio-Based Finite Element Method - Lusi Dwi Putri; Violla De Boyosa (Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
The landslide disaster in Nagari Aia Dingin, Lembah Gumanti District, Solok Regency is strongly associated with anthropogenic and natural factors, particularly mining activities and prolonged high-intensity rainfall. These conditions have significantly altered slope geometry and reduced soil stability. This study aims to evaluate soil characteristics, determine the factor of safety, and propose appropriate mitigation strategies for slope failure. A quantitative approach was adopted through laboratory testing and numerical simulation using GeoStudio. The results indicate that the soil is classified as silty sand with poor gradation. The calculated factor of safety values under slope variations of 30°, 45°, and 60° are consistently below 1.5, indicating unstable slope conditions. Therefore, the study highlights the urgent need for slope stabilization measures to mitigate future landslide risks.